2018
DOI: 10.1017/s1041610218000030
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of geriatric depression in rural China based on a generalized estimating equation

Abstract: Geriatric depression in rural China was associated with several socio-demographic, physical, and mental factors. Targeted interventions are essential to improve the psychological health of aged individuals in rural China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
19
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 35 publications
8
19
4
Order By: Relevance
“…However, previous studies have suggested that patients with high education levels are more likely to have better medical and disease condition knowledge and are thus less likely prone to anxiety, depression and other negative emotions caused 2798 by errors and negative news than those with low education levels; accordingly, they can actively respond to and positively face the difficulties in front of them. 34 We think that the reason why the results of this study were different from those of previous studies may be related to differences in the cultural levels of patients. The logistic regression analysis showed that introversion was a risk factor for the development of ASD in EPOFs, and introverts are more likely to have ASD than extroverts.…”
Section: Discussioncontrasting
confidence: 82%
“…However, previous studies have suggested that patients with high education levels are more likely to have better medical and disease condition knowledge and are thus less likely prone to anxiety, depression and other negative emotions caused 2798 by errors and negative news than those with low education levels; accordingly, they can actively respond to and positively face the difficulties in front of them. 34 We think that the reason why the results of this study were different from those of previous studies may be related to differences in the cultural levels of patients. The logistic regression analysis showed that introversion was a risk factor for the development of ASD in EPOFs, and introverts are more likely to have ASD than extroverts.…”
Section: Discussioncontrasting
confidence: 82%
“…This study revealed that 13.6% of the general public suffered from depression during the early stages of the pandemic of COVID-19 in China. The prevalence of depression was slightly lower than the prevalence before the outbreak of COVID-19 from previous studies [ 56 - 58 ] (13.8% vs 18.8%). The results also indicated that the prevalence of depression during the COVID-19 pandemic is almost identical to that during the SARS epidemic (11.9% vs 18.0%) among the general public in China [ 59 , 60 ].…”
Section: Discussioncontrasting
confidence: 66%
“…Our results accord with the previous findings of risk factors for depression among older Chinese adults. [33][34][35][36][37][38][39][40][41][42][43] Higher severity grades in age, number of chronic diseases, and living area (gross and per capita) each independently increase probable and possible depression among rural older adults in China. Studies conducted in urban China indicated the same patterns in rural areas.…”
Section: Open Accessmentioning
confidence: 99%